Implementasi Konsep “Kudus Explore : Exploring With Experiencing” pada Perancangan Interior Museum Kebudayaan Kudus - Iriene Cahyani Santoso; Ronald Hasudungan Irianto Sitindjak; Stephanie Melinda Frans (Intra, 2019)
Kudus is known as a region that has abundant historical and cultural records, yet there hasn’t been a place which can accommodate and represent the city of Kudus as a whole. The thematic museum available is still conventional. Therefore the Kudus Cultural Museum is designed with a recreational, educational, and interactive look. The method used is Design Thinking Method which uses three stages, which are Inspiration, Ideate and Implementation. The design concept for the Kudus Cultural Museum is "Explore Kudus : Exploring and Experiencing". This concept creates an innovation for a new museum appearance, by providing experiences for visitors to be able to enjoy their trip exploring Kudus City. Sensory experiences are applied in the design. Visitors are invited to be able to know, be involved and experience the vibes of Kudus City.